Do As I Say, Not As I Do: Benevolent Deception in Romantic Relationships. (14th August 2014) - Hart, Christian L.; Curtis, Drew A.; Williams, Nicole M.; Hathaway, Marissa D.; Griffith, James D.
Abstract : In this study, men and women were surveyed about their attitudes toward the use of white lies and other forms of benevolent deception in their romantic relationships. We predicted that people would be more accepting of telling lies than of having lies told to them. Furthermore, we predicted that women would be more accepting than men of benevolent deception in their romantic relationships. We found that people were more tolerant of telling benevolent lies than they were of being told such lies. However, we found that men, not women, were more accepting of benevolent deception in their relationships.